Crustal thickness and vP/vS ratio and their tectonic implication in Jilin Province - Chuang Chen; Zigen Wei; Xintian Fan; Zhiwei Cheng; Qi Deng; Miao Sun (地震科学进展)
Using data on crustal thickness and the vP/vS ratio calculated from teleseismic waveforms recorded at five temporary stations and collected from previous studies in Jilin Province, we analyzed the crustal structure in different geological units. The results show that the average crustal thickness in Jilin Province is 32.57 km with thinner crust in the middle; the average vP/vS is 1.768 with higher values in the eastern region; crustal thickness in Changbai Mountain area is higher than that in the Songliao Basin, whereas the vP/vS ratio is lower than that in the Songliao Basin. The crustal thickness in the Changbai Mountain area is thin in the west, the vP/vS ratio shows small variation, and the thin crust with the high vP/vS ratio appear in the volcanic eruption area. In the Songliao Basin area, the crust is thin in the east with a high vP/vS ratio, whereas the Songyuan and Qianguo areas with dense earthquakes exhibit substantial lateral changes in crustal thickness and high vP/vS ratios. The thinnest crust and the highest vP/vS ratio is found in the Songyuan area in Jilin Province.